2016
DOI: 10.1007/s00784-016-1923-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cognitive and masticatory function in Alzheimer’s disease

Abstract: Knowledge that mild AD has an impact on chewing is important for dental professionals in decision-making related to prosthetics and general dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…This finding may be explained by differences between urban and rural lifestyles, availability of medical resources and convenience of medical access [ 3 , 40 ]. Patients with AD also exhibit impairments in chewing function due to progressive neurodegeneration, increasing the risk of periodontal problems [ 41 , 42 ]. Hence, proper dental care and oral rehabilitation are necessary to improve masticatory function in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by differences between urban and rural lifestyles, availability of medical resources and convenience of medical access [ 3 , 40 ]. Patients with AD also exhibit impairments in chewing function due to progressive neurodegeneration, increasing the risk of periodontal problems [ 41 , 42 ]. Hence, proper dental care and oral rehabilitation are necessary to improve masticatory function in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the association between masticatory performance and cognitive conditions, we performed a review by systematically searching for and screening the original studies that directly investigated the association between cognitive decline and masticatory ability using a masticatory performance test (Table 2 ). We found five studies published in the past five years that objectively quantified masticatory performance using functional assessments, including the color-changeable chewing gum test [ 34 , 35 ], the two-color chewing gum test [ 36 , 37 ], and the Optocal chewing test and the sieve fractionation test [ 38 ]. Masticatory performance decreased in patients with dementia compared to the controls [ 36 , 38 ] and was associated with performance on cognitive tests [ 34 , 35 , 37 ] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies also highlight the correlation between tooth loss and the worsening of dementia in older adults, and it has been reported that chewing efficiency with a dental prosthesis decreases by 30–40%. For example, Campos et al . discovered a correlation between masticatory function and cognitive decline in mild AD, partially edentulous subjects, compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies also highlight the correlation between tooth loss and the worsening of dementia in older adults, and it has been reported that chewing efficiency with a dental prosthesis decreases by 30-40% 4,33,34 . For example, Campos et al 21 discovered a correlation between masticatory function and cognitive decline in mild AD, partially edentulous subjects, compared with a control group. However, limited evidence links these variables and cerebral blood flow during mastication, but some results show a significant activation of the PFC when participants used a dental prosthesis, and it is proposed that rehabilitation may be effective in prevention of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation